Anti-termite and anti-fungal activity test of ethanolic extract of Melastoma malabathricum leaves - Hikma Yanti; Yeni Mariani; Fathul Yusro; Alkhadi (Talenta Publisher, 2026)
Wood damage caused by the ground termite Coptotermes curvignathus and the rotting fungus Schizophyllum commune is a major problem in the tropics. This study aims to evaluate the anti-termite and anti-fungal activity of the ethanol extract of Melastoma malabathricum leaves as a natural wood preservative. Extraction was carried out by the maceration method, and the extracts were tested at 2–10% concentration using a Complete Random Design with three replicates. Termite mortality and weight loss of the test paper were observed for 21 days, while inhibition of fungal growth was observed for 7 days. Data were statistically analyzed using the nonparametric Kruskal-Wallis test and the Pairwise Comparisons follow-up test with Bonferroni correction at 95% confidence level (p<0.05). The results showed that extract concentration significantly increased termite mortality (p = 0.005) and anti-fungal activity (p = 0.006). However, the treatment had no significant effect on test paper weight loss (p = 0.072). The 10% concentration resulted in the highest termite mortality (36.36%) and the highest anti-fungal activity (88.23%), and was the only treatment to show a statistically significant difference compared with the control. Based on follow-up test results, a 10% concentration is recommended as optimal due to its clear effectiveness in providing biological protection. These results show that the ethanol extract of Melastoma malabathricum leaves has the potential to serve as an environmentally friendly natural wood preservative